Hemp Fertilization: Current Knowledge, Gaps and Efforts in Florida: A 2020 Report - Rao S. Mylavarapu; Zachary Brym; Luis Monserrate; Michael J. Mulvaney (EDIS)
Hemp is an annual herbaceous plant that may be grown for fiber, seed, or flowers. Starting in April 2020, the Florida Department of Agriculture and Consumer Services began accepting applications for cultivation of hemp in Florida, with the potential for building a $20–$30 billion industry in the state. The statewide UF/IFAS Industrial Hemp Pilot Project is researching aspects of agronomic production for hemp cultivation. While a few other state soil testing laboratories provide soil tests and nutrient recommendations based on research and experience, at this time no Florida-specific data on nutrient requirements and fertilization are available. This new 5-page article, written by Rao Mylavarapu, Zachary Brym, Luis Monserrate, and Michael J. Mulvaney and published by the UF/IFAS Department of Soil and Water Sciences, provides a summary of published and personal communications from different states on hemp fertilization. https://edis.ifas.ufl.edu/ss689